2009
DOI: 10.5194/hess-13-1809-2009
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tree roots for preferential infiltration in stagnic soils

Abstract: Abstract. It is generally recognized that roots have an effect on infiltration. In this study we analysed the relation between root length distributions from Norway spruce (Picea abies (L.) Karst), silver fir (Abies alba Miller), European beech (Fagus sylvatica L.) and preferential infiltration in stagnic soils in the northern Pre-Alps in Switzerland. We conducted irrigation experiments (1 m 2 ) and recorded water content variations with time domain reflectometry (TDR). A rivulet approach was applied to charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 36 publications
(46 reference statements)
5
57
0
Order By: Relevance
“…In our study, soil hydraulic conductivity closely correlated to root mass density (P<0.05). This result agrees with the conclusions of Lange et al (2009), who found that high root densities resulted in densely branched networks of pores and enhanced soil infiltrability.…”
Section: Factors Impacting the Soil Infiltration Processsupporting
confidence: 93%
“…In our study, soil hydraulic conductivity closely correlated to root mass density (P<0.05). This result agrees with the conclusions of Lange et al (2009), who found that high root densities resulted in densely branched networks of pores and enhanced soil infiltrability.…”
Section: Factors Impacting the Soil Infiltration Processsupporting
confidence: 93%
“…Microbiological activity stimulates root development, plant growth and vice versa (Cheng and Coleman, 1990;Fu and Cheng, 2002;Vessey, 2003). The plant regrowth protects the soil from raindrop impact ) and root development creates new pathways and preferential water flow, increasing the water infiltration (Lange et al, 2009). The invertebrates' activity may also have contributed to the reduction of soil hydrophobic compounds and changed the hydraulic conductivity in the burned plot studied (Fig.…”
Section: Soil Water Repellencymentioning
confidence: 99%
“…Finally, root characteristics of the facility of interest can be compared to values found in this (Table 9) and other work (Nassif and Wilson 1975, Day et al 2000, Bharati et al 2002, Devitt and Smith 2002, Zhou and Shangguan 2007, Bratieres et al 2008, Bartens et al 2008, Lange et al 2009). As root characteristic values shown in this work mostly overlapped with values shown in similar studies, managers can use these values (Table 9) as lower thresholds at which point roots may be enhancing infiltration at their site.…”
Section: Potential For Root-enhanced Infiltration Within Sbfsmentioning
confidence: 99%
“…Root Processing: Each core was weighed, wrapped in cellophane (Kokko et al 1993), stored at 4°C temporarily in a dark fridge, and then processed within 24 hr after extraction (Smit 2000, Lange et al 2009). Root cores were cut into 8.4 cm increments with 720 total sections processed.…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation